Cardiovascular adverse events and immune-related adverse events associated with PD-1/PD-L1 inhibitors for head and neck squamous cell carcinoma (HNSCC) - Adila Abulizi; Guangpeng Yan; Qian Xu; Reyihanguli Muhetaer; Shihan Wu; Kudelaiti Abudukelimu; Xi Chen; Chengjiang Liu; Jun Li (Scientific Reports, 2024)
Abstract While some literature has provided limited information about the potential cardiovascular risk and immune-related adverse events (irAEs) risk associated with PD-1/PD-L1 inhibitors in the treatment of Head and Neck Squamous Cell Carcinoma (HNSCC), the exact relevance is still uncertain. To assess the pharmacovigilance (PV), constituent ratio, severity, and reaction outcomes of major adverse cardiovascular events (MACE) and immune-related adverse events (irAEs) related to PD-1/PD-L1 inhibitors for HNSCC reported to the United States Food and Drug Administration Adverse Event Reporting System (FAERS). We analyzed reports of cardiovascular adverse events and irAEs associated with drug therapy for HNSCC submitted to FAERS from the 1st quarter 2015 to the 3rd quarter of 2023. Three PD-1/PD-L1 inhibitors were identified: nivolumab, pembrolizumab and durvalumab. Our primary composite endpoint was the PV of MACE and irAEs related to PD-1/PD-L1 inhibitors in the treatment of HNSCC, and the secondary endpoint was PV of other cardiovascular events. The software implemented was STATA 17.0 MP. 19,372 suspected drug-adverse event reports related to drug treatment in patients with HNSCC were identified, of which 916 reports were cardiovascular events, including 555 reports of MACE and 361 reports of other cardiovascular events. The PV signal regarding MACE was detected in durvalumab (PRR  = 2.12, 95% CI: 1.24–3.61; χ2  = 7.71; ROR  = 2.19, 95% CI: 1.24–3.86; IC  = 1.01; IC025  = 0.07) but not in nivolumab and pembrolizumab. The constituent ratio of MACE in all adverse events caused by nivolumab (OR  = 0.38, 95% CI: 0.19–0.73) and pembrolizumab (OR  = 0.48, 95% CI: 0.23–0.99) was significantly decreased, compared with durvalumab. A PV signal about other cardiovascular events was detected in durvalumab (PRR  = 3.04, 95% CI: 1.73–5.31; χ2  = 16.13; ROR  = 3.15, 95% CI: 1.74–5.70; IC  = 1.46; IC025  = 0.48), but it was not detected in nivolumab or pembrolizumab. The constituent ratio of other cardiovascular events in all adverse events caused by nivolumab (OR  = 0.25, 95% CI: 0.13–0.48) and pembrolizumab (OR  = 0.40, 95% CI: 0.20–0.80) was significantly decreased, compared with durvalumab. The constituent ratio of other cardiovascular events in all adverse events caused by nivolumab (OR  = 0.61, 95% CI: 0.38–0.99) was significantly decreased, compared with pembrolizumab. There were 40 cases of hypertension. A PV signal about hypertension was detected in pembrolizumab (PRR  = 3.72, 95% CI: 1.87–7.43; χ2  = 15.99; ROR  = 3.75, 95% CI: 1.87–7.51; IC  = 1.53, IC025  = 0.45), but it was not detected in nivolumab. The constituent ratio of hypertension in all adverse events caused by nivolumab (OR  = 0.09, 95% CI: 0.09–0.39) was significantly decreased, compared with pembrolizumab. There were 737 cases of irAEs. A PV signal about irAEs was detected in nivolumab (PPR  = 1.27, 95% CI: 1.05–1.53; χ2  = 6.38; ROR  = 1.28, 95% CI: 1.06–1.56; IC  = 0.29, IC025  = −0.00) and pembrolizumab (PPR  = 2.20, 95% CI: 1.79–2.71; χ2  = 56.55; ROR  = 2.31, 95% CI: 1.84–2.88; IC  = 1.03; IC025  = 0.68), but it was not detected in durvalumab. The constituent ratio of irAEs in all adverse events caused by nivolumab (OR  = 0.58, 95% CI: 0.44–0.76) significantly decreased, compared with pembrolizumab. By comparing the PV signals, constituent ratio, severity, and reaction outcome of the three drugs, we suppose that nivolumab can be used as the safest PD-1/PD-L1 inhibitor for HNSCC.